An Optimum Condition of Surface Modification Improving the Dispersity of Nano-Silica in Organic Solvents Using 2-Propenoic-2-methyl-3- trimethoxysilyl-propyl Ester Water Solution - Li, Yulin; Chen, Zhengxing; Li, Xiaoxuan; Zeng, Huawei (Asian Journal of Chemistry, 2010)
Surface modification improving the dispersity of the prepared nano-silica in organic solvents using different concentrations and amounts of 2-propenoic-2-methyl-3-trimethoxysilyl-propyl ester in aqueous solution were investigated. The result suggested that the optimum modification condition was that the concentration of 2-propenoic-2-methyl-3-trimethoxysilyl-propyl ester in aqueous solution was 0.4 mol/L and the amount of 2-propenoic-2-methyl-3-trimethoxysilylpropyl ester water solution was 30 mL/10 g nano-silica. The dibutyl phthalate absorption number of the optimum modified nano-silica was 3.5 cm3/g. The result from Fourier transform infrared suggested that the surface of the prepared nano-silica was modified by 2-propenoic-2-methyl-3- trimethoxysilyl-propyl ester water solution (0.4 mol/L, 30 mL/10 g nano-silica). X-Ray diffraction further indicated that the prepared nano-silica was modified by surface modification using 2- propenoic-2-methyl-3-trimethoxysilyl-propyl ester water solution (0.4 mol/L, 30 mL/10 g nanosilica). Transmission electron microscopy images revealed that the dispersity of the prepared nano-silica in organic solvents was obviously improved. The data of the dispersity of the prepared nano-silica and the optimum modified nano-silica in many organic solvents further demonstrated that the dispersity of the prepared nano-silica in organic solvents was improved by surface modification using 2-propenoic-2-methyl-3-trimethoxysilyl-propyl ester water solution (0.4 mol/ L, 30 mL/10 g nano-silica).